Pengaruh Citra Merek dan Persepsi Kualitas terhadap Loyalitas Pelanggan Melalui Kepuasa Pelanggan pada Burger King Selama Pandemi Covid-19: - Ninda Renatha Indraswari,; Ety Dwi Susanti (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the effect of brand image and perceived quality on customer loyalty through customer satisfaction. This research was conducted at Burger King Sidoarjo in 2022. This type of research is quantitative research with 100 respondents and the sampling technique used is purposive sampling technique, namely sampling by giving certain criteria to the sample. Data collection techniques were carried out by means of questionnaires. The analytical technique used in this research is path analysis through SPSS25 for Windows. The results of this study indicate that partially brand image does not have a significant effect on customer satisfaction while perceived quality has a significant effect, then brand image and customer satisfaction have no significant effect on customer loyalty, while perceived quality has a significant effect. In addition, customer satisfaction cannot mediate brand image on customer loyalty while customer satisfaction can mediate perceived quality on customer loyalty. Keywords: Brand Image;Customer Satisfaction;Customer Loyalty;Perceived Quality